Data Mining Dalam Penentuan Pemesanan Buku Perpustakaan UAD dengan Menggunakan Metode Naïve Bayes - Muhammad Iqbal Hadiwibowo; Faisal Fajri Rahani (Universitas Budi Darma, 2022)
Library Universitas Ahmad Dahlan (UAD) has not utilized technology in the book ordering process. The process of ordering books from distributors requires many considerations such as the number of requests, recommendations for study programs, location, year and language. This consideration made the UAD Library take more than 2 weeks in the book selection process. This study aims to apply data mining in determining book orders using the Naïve Bayes method. This study uses 1106 book procurement data for the past year with criteria, namely the number of requests, study program recommendations, location, year, and language. Implementation of data mining using the Naïve Bayes algorithm is carried out in stages including data cleaning, data selection, data transformation, sharing of training data and data testing, implementation and results of the Nave Bayes algorithm and system testing. System testing using the Confusion Matrix method. Based on the Confussion Matrix calculation on the testing data, the accuracy is 90.24%, the precision is 89.69%, the recall is 93.54%, the specificity is 91.04%, and the F1 score is 91.57%. It was concluded that the system test results were said to be good.